1994
DOI: 10.1111/j.1570-7458.1994.tb01830.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in the reactive distance in Trichogramma brassicae after automatic tracking of the walking path

Abstract: Efficiency of hymenopterous parasitoids to control pests in a biological control release program probably increases with increasing searching ability of the females, which, in return, likely depends on the distance from which females perceive their hosts (i.e., reactive distance). In this study, we first analyse this hypothesis with the help of a stochastic model simulating the walking path of isolated Trichogramma females during their searching behaviour. Then, this reactive distance is estimated using automa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…Consequently, the insect switched from an extensive to a so-called intensive walking behaviour. Roitberg (1985) and Bruins et al (1994) defined the reactive distance as the minimal distance from which the insect can detect the presence of any resource item (or chemical compound). The algorithm thus includes the ability of the insect to laterally detect, during its walking behaviour, the presence of kairomones (or eggs) within a distance of one cell (i.e.…”
Section: Walking Behavioursmentioning
confidence: 99%
“…Consequently, the insect switched from an extensive to a so-called intensive walking behaviour. Roitberg (1985) and Bruins et al (1994) defined the reactive distance as the minimal distance from which the insect can detect the presence of any resource item (or chemical compound). The algorithm thus includes the ability of the insect to laterally detect, during its walking behaviour, the presence of kairomones (or eggs) within a distance of one cell (i.e.…”
Section: Walking Behavioursmentioning
confidence: 99%
“…Using a stochastic model simulating the walking path of isolated parasitoid females during their searching behaviour, Bruins et al (1994) have shown that this trait is indeed correlated with the wasp's efficiency to discover new hosts. These authors demonstrated that, whatever the host spatial distribution, an increase in the reactive distance leads to a strongly significant increase in the number of hosts discovered per unit of time.…”
Section: Introductionmentioning
confidence: 99%
“…This trait was estimated by several authors usually using indirect methods based on percentage parasitism (Laing, 1937(Laing, , 1938Edwards, 1961;Holling, 1966;Yano, 1978). More recently, a more direct way to estimate this trait was proposed after analyzing the recorded walking paths of foraging females (Pak et al, 1991;Bruins et al, 1994;Wajnberg and Colazza, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Documentation of genetic variation in foraging behavior is also important for understanding the process of evolution, and may be important for selection and application of natural enemies in biological control (Mackauer, 1976;Lewis and Martin, 1990;Hopper et al, 1993;Bruins et al, 1994). Genetic variation in components of search behavior has been reported in predatory arthropods and parasitoids (Hoy, 1990;Hopper et al, 1993;Bruins et al, 1994;Gu and Dorn, 2000). Previous studies on attraction of P. persimilis to volatiles produced by prey-infested lima bean plants suggested considerable phenotypic variation in predator responsiveness (Margolies et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Assessing genetic variation in the response of natural enemies to plant-derived volatiles is the first step to understanding the role of this response in predator-prey dynamics (Dicke et al, 1990a, b;Lewis and Martin, 1990;Vet and Dicke, 1992). Documentation of genetic variation in foraging behavior is also important for understanding the process of evolution, and may be important for selection and application of natural enemies in biological control (Mackauer, 1976;Lewis and Martin, 1990;Hopper et al, 1993;Bruins et al, 1994). Genetic variation in components of search behavior has been reported in predatory arthropods and parasitoids (Hoy, 1990;Hopper et al, 1993;Bruins et al, 1994;Gu and Dorn, 2000).…”
Section: Introductionmentioning
confidence: 99%